The Appropriateness of Empirical Uses of Antibiotics Based on Antimicrobial Susceptibility Results for Inpatients at a Tertiary Hospital in Saudi Arabia - Yasser Almogbel; Mugahid A. Mobark; Masaad S. Almutairi; Faisal S. Almogbel; Syed I. Rabbani; Sultan Alhathloul; Shada Alamro; Lateefah Alatallah (MDPI AG, 2024)
The optimal use of antibiotics represents a cornerstone in controlling antibiotic resistance. Strategies such as antibiotic stewardship programs (ASPs) have been developed to influence the rational use of antibiotics. This study evaluated the appropriateness of the empirical use of antibiotics based on antibiotic susceptibility results with the aim of participating effectively in improving local ASPs. In a cross-sectional study conducted at a tertiary hospital in Saudi Arabia, 500 inpatients received empirical antibiotics, and their culture and sensitivity results were included. The appropriateness of the empirical use of antibiotics was determined based on their alignment with the culture and sensitivity results. More than half of the participants (56.4%) were men, and nearly half (43%) were over 61 years old. The empirical uses of antibiotics were appropriately prescribed in 58% of the patients. Ciprofloxacin and ceftriaxone were the most prescribed antibiotics, while vancomycin, piperacillin-tazobactam, and tigecycline were the most appropriately prescribed antibiotics. E. coli was the main microorganism isolated in the susceptibility results and was appropriately prescribed in 59% of the patients. The highest microbial sensitivity was observed for linezolid, vancomycin, and tigecycline. Antibiotics were appropriately prescribed empirically in more than half of the participants. Activating interventional ASP is crucial to fill the gap in prescribing antimicrobials. Considering the expected type of organisms and the local susceptibility pattern is likely to yield a more appropriate empirical use of antibiotics.